DEVELOPMENT OF SOCIAL SCIENCE LEARNING BASED ON ETHNOPEDAGOGY AS A PROGRAM FOR STRENGTHENING LOCAL VALUES - Deny Setiawan (Sensei International Journal of Education and Linguistic, 2021)
This research was by the factual condition of the occurrence of a value crisis among the younger generation on the pride of local wisdom values. This study was aimed to develop ethnopedagogy-based Social Science learning as a program to strengthen local wisdom values at the Faculty of Social Sciences, Universitas Negeri Medan. The research method was the R&D method following the Borg & Gall procedure. The research subjects involved: (1) lecturers and students of the Faculty of Social Sciences, Universitas Negeri Medan; and (2) six expert validators. The instrument was used an expert validation questionnaire which was analyzed using the Percentage Mean Score (PRS). The research results showed that the social studies textbooks based on local wisdom developed were very valid. Other findings were based on the test results showed that ethnopedagogy-based Social Science learning could strengthen the values of local wisdom that exist in Indonesia in a global era filled with value paradoxes.